2014
DOI: 10.1098/rspb.2014.0629
|View full text |Cite
|
Sign up to set email alerts
|

Early-life exposure to a herbicide has enduring effects on pathogen-induced mortality

Abstract: Early-life exposure to a herbicide has enduring effects on pathogeninduced mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…Under this hypothesis, the frogs from the no-salt exposure, low-density treatment would have had stronger immune defenses and consequently higher survival than the frogs from the other 3 treatments. Consistent with this hypothesis is the reduced immune defenses in postmetamorphic salamanders exposed to contaminants as larvae [5]. Other studies, however, found no evidence for carryover effects after larval exposure to atrazine, carbaryl, or malathion in the terrestrial life stages of amphibians [15,42].…”
Section: Discussionmentioning
confidence: 92%
“…Under this hypothesis, the frogs from the no-salt exposure, low-density treatment would have had stronger immune defenses and consequently higher survival than the frogs from the other 3 treatments. Consistent with this hypothesis is the reduced immune defenses in postmetamorphic salamanders exposed to contaminants as larvae [5]. Other studies, however, found no evidence for carryover effects after larval exposure to atrazine, carbaryl, or malathion in the terrestrial life stages of amphibians [15,42].…”
Section: Discussionmentioning
confidence: 92%
“…For example, many pesticides are immunomodulators that can increase infectious diseases of wildlife and humans 82,83 , or are endocrine disruptors of humans with potential downstream effects on immunity 84 . Even if pesticides do not directly affect immunity, detoxification of pesticides is energetically 'expensive' for the host, and thus pesticide exposure can reduce available energy resources for humans and zoonotic hosts to invest into parasite defences 85,86 .…”
Section: Drugs Use Agrochemicals and Infectious Diseasementioning
confidence: 99%
“…Although, a causal link between pesticide exposure and disease outbreaks has not been identified in the laboratory or in the field (Paetow et al, 2012;Rohr et al, 2013), it is still an intriguing relationship worth continued investigations. Pesticides have the potential to increase susceptibility (Mann et al, 2009) while elevated nutrient concentrations have the potential to increase the incidence of disease in amphibian populations (Johnson et al, 2007).…”
Section: Potential Impacts To Amphibiansmentioning
confidence: 99%